I'll always love you - Wilhelm, Hans 1945- (New York Crown, 1985)
A child's sadness at the death of a beloved dog is tempered by the remembrance of saying to it every nignt, "I'll always love you."
Keywords: Dogs -- Fiction; Death -- Fiction